The Perspectives of Master's Students on the Importance of Ushul Nahwu in Learning Arabic as a Foreign Language - Rizqia, Ana Sabila; Dienana, Arina; Sopian, Asep (Al-Fusha : Arabic Language Education Journal, 2024)
This study aims to explore students’ perspectives on the relevance of learning ushul nahwu in the modern era. A descriptive qualitative approach was used with data collection methods through interviews and questionnaires involving all students who had taken the course. The results showed that most students considered ushul nahwu theoretically important, especially for prospective Arabic language teachers, but they felt the ushul nahwu material needed to be revised to be more relevant to modern needs. Although most students recognized the benefits of ushul nahwu in understanding Arabic grammar, only a small number felt that the course provided practical benefits in their Arabic language skills. Some students have difficulty understanding the concepts of ushul nahwu and applying them in Arabic language learning. Overall, the results indicate the need for a review of the ushul nahwu curriculum to better suit the needs of Arabic language learning in the modern era, with an emphasis on practical aspects and relevance to the times.